A Brønsted‐Ligand‐Based Iron Complex as a Molecular Switch with Five Accessible States. Issue 17 (20th March 2019) - Shiga, Takuya; Saiki, Ryo; Akiyama, Lisa; Kumai, Reiji; Natke, Dominik; Renz, Franz; Cameron, Jamie M.; Newton, Graham N.; Oshio, Hiroki
Abstract: A mononuclear Fe II complex, prepared with a Brønsted diacid ligand, H2 L (H2 L=2‐[5‐phenyl‐1 H ‐pyrazole‐3‐yl] 6‐benzimidazole pyridine), shows switchable physical properties and was isolated in five different electronic states. The spin crossover (SCO) complex, [Fe II (H2 L)2 ](BF4 )2 (1A ), exhibits abrupt spin transition at T 1/2 =258 K, and treatment with base yields a deprotonated analogue [Fe II (HL)2 ] (1B ), which shows gradual SCO above 350 K. A range of Fe III analogues were also characterized. [Fe III (HL)(H2 L)](BF4 )Cl (1C ) has an S =5/2 spin state, while the deprotonated complexes [Fe III (L)(HL)], (1D ), and (TEA)[Fe III (L)2 ], (1E ) exist in the low‐spin S =1/2 state. The electronic properties of the five complexes were fully characterized and we demonstrate in situ switching between multiple states in both solution and the solid‐state. The versatility of this simple mononuclear system illustrates how proton donor/acceptor ligands can vastly increase the range of accessible states in switchable molecular devices. Abstract : Switch that : A mononuclear Fe II complex prepared with an asymmetric Brønsted ligand exhibited multi‐state switchable properties and was isolated in five distinct electronic states. By modifying the degree of protonation, both spin‐ and redox‐interconversion was observed, resulting in a range of tunable magnetic, electrochemical, and optical properties. SCO=spin crossover.